Factors that Influence Generation Z in Consuming Honey at FPPK Bangka Belitung University - Risqah Muthia; Evahelda Evahelda; Yulia Yulia (Journal of Global Sustainable Agriculture, 2025)
Honey is one of the natural ingredients that has many benefits for the body, making it often used as a health supplement. Generation Z is part of a generation that requires additional supplements to support their academic and non-academic activities. This study aims to: (1) Identify the characteristics of Generation Z as honey consumers at FPPK, Universitas Bangka Belitung, (2) Analyze the factors influencing Generation Z in consuming honey at FPPK, Universitas Bangka Belitung. The research method used is a survey method with a purposive sampling approach. The sample size in this study consists of 100 students who have consumed honey. Data were collected through structured interviews and open-ended questionnaires, then analyzed using a descriptive qualitative approach. The results of the study indicate that: (1) The characteristics of honey consumers are mostly students aged 21-22 years, predominantly female, with a monthly allowance ranging from Rp500,000 to Rp1,000,000. They consume honey irregularly, with a frequency of 1-2 times per month and a dosage of 2 tablespoons per consumption. In terms of price, students tend to choose honey within the price range of >Rp50,000-Rp100,000, which is obtained from parents/family or supermarkets. (2) The factors influencing the consumption of honey among Generation Z at FPPK, Universitas Bangka Belitung, include social class, habits, health knowledge, and product attributes. Meanwhile, factors that do not influence honey consumption are monthly allowance and location.